Some Contributions of Organic Chemistry to the Study of the Biosynthesis of Natural Products. (May 2017) - Hanson, James R.
The development over the last 100 years of organic chemists' contributions to the understanding of the biosynthesis of natural products is reviewed. The transitions from speculation to labelling experiments and to the current role of genomics are exemplified, particularly from terpenoid biosynthesis.